The glassmaker [large type] - Chevalier, Tracy (Thorndike Press large print top shelf., 2024)
"It is 1486 and Venice is a wealthy, opulent center for trade. Orsola Rosso is the eldest daughter in a family of glassblowers in Murano, the island revered for the craft. As a woman, she is not meant to work with glass--but she has the hands for it, the heart, and a vision. When her father dies, she teaches herself to make beads in secret, and her work supports the Rosso family fortunes. Skipping like a stone through the centuries, in a Venice where time moves as slowly as molten glass, we follow Orsola and her family as they live through creative triumph and heartbreaking loss. In every era, the Rosso women ensure that their work, and their bonds, endure." --